National and Regional Supreme Audit Institutions’ Contribution During COVID-19 Pandemic - Ivana MAMIC SACER (Communications of International Proceedings, 2021)
Supreme audit institutions play an important role in ensuring transparency and accountability in public sector. Today, in the global pandemic environment, this role has become even more significant. International and regional audit institutions offer a support to supreme audit institutions in these difficult time. 2020 year was marked by the COVID-19 business environment and governmental restriction measures in dealing with saving human lives. The goal of the paper is to argue about the role of national and regional supreme audit institutions in operating with the COVID- 19 environment. The paper deals with three perspectives of SAIs in COVID-19 environment. First objective of the paper was to explore the existing framework for state audit to find out the solutions for SAIs operation in pandemic. Further, the role of regional SAIs was explored in order to find out possible ways of such institutions support to national SAIs. Finally, the paper argues about lessons learned from past disaster audits. Research results show that the ISSAI professional pronouncements could help SAIs in doing business during and after pandemic. Other than that, regional SAIs offer great help in sharing knowledge and experience in the form of web site materials, webinars, conferences, blogs and articles in newspapers. National SAIs can benefit also from the experience from past disaster audits since the disaster management cycle and disaster risks are similar.
Keywords: COVID-19; Disaster Audit; INTOSAI; Supreme Audit Institution